Perception of medical students towards online learning during COVID-19 pandemic: a cross-sectional study in South Kerala, India - Kuriakose, Allen; Abraham, Joe; Kurian, Nisha; Mathew, Elsheba (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) pandemic has brought major changes in every sector including education. From school to college level, traditional classroom learning was forced to change to online learning. There were many challenges from inexperience to mental and physical health issues. This study aimed to find the perception of medical students about current medical online learning system in south Kerala. Methods: An online survey was conducted in November 2020 using a self-designed pretested questionnaire consisting of three sections: socio demographic profile, a 4-point Likert scale having 29 items to assess the perception of online learning, questions to assess certain parameters like health problems, duration of electronic usage etc. Frequencies, percentages, and descriptive statistics were calculated, and Chi-square test was used for statistical significance. Results: Study showed nearly three-fourth (74%) of students have a negative perception towards online learning. Of the different formats of e-learning used by students during the study period, most preferred were live lectures. Among the participants, more than half (57%) suggested a need for improvement in the quality of classes. Majority (75%) of students agreed that long hours of online classes had caused health problems. Conclusions: Though online learning is the need of the hour; majority of the students have a negative perception towards it which demands an enhancement in its standards and change to a preferred format